The influence of impact modelling assumptions on the dynamic behaviour of flexible rocking oscillators - Zhu, H; Chatzis, M; Acikgoz, S (European Community on Computational Methods in Applied Sciences, 2021)
For rigid rocking models, energy dissipation relies solely on impact. Consequently, the position of the impulse acting on the rocking body determines the magnitude of energy loss and strongly influences the subsequent dynamic response. This paper evaluates the corresponding influence of the location of the vertical impulse on the dynamic behaviour of flexible rocking oscillators. The dynamic behaviour of a rocking flexible oscillator is explored in this study with an impact model that parametrically considers the position of impulse. The influence of the position of impulse on the expected energy loss during impact, and on the overturning stability of the flexible rocking oscillator are then examined. It is shown that the energy loss at impact reduces and the potential for overturning instability increases, for impulses located at increasing distances from the future rocking corner.